The expression and clinical value of GNA13 in invasive placenta accreta spectrum disorders - GAN Yanping; HUANG Liyun; TANG Na; MA Youliang; HUANG Zhiguang; LONG Yu (Guangxi Yike Daxue xuebao)
Objective To investigate the expression and significance of Guanine nucleotides binding protein alpha 13 (GNA13) in the late pregnancy peripheral blood and placental tissue of patients with invasive placenta accreta spectrum disorders (PAS). Methods A case-control study method was used. Patients diagnosed with PAS by clinical and pathological examination at the First Affiliated Hospital of Guangxi Medical University from September 2021 to June 2023 formed the study group (PAS group, n=32), and the control group (n=32) consisting of cesarean section pregnant women without PAS, was matched according to the gestational age at delivery, placental location, history of cesarean section and the presence of concurrent medical diseases. Enzyme-linked immunosorbent assay (ELISA) was used to detect the serum GNA13 levels, and immunohistochemistry assay (IHC) and western blotting were used to detect the placental GNA13 expression. Receiver operating characteristic (ROC) curve was used to analyze the diagnostic efficacy of GNA13. Results The expression level of GNA13 in the peripheral blood of the PAS group was significantly higher than that in the control group (P＜0.05). The area under the ROC curve (AUC) was 0.734 (95% CI: 0.593-0.876). The optimal threshold for distinguishing PAS with blood GNA13 was 201.53 ng/ml, with a sensitivity of 96% and a specificity of 52%. GNA13 was localized in the trophoblast cells of the placental villi. The expression of GNA13 in the placenta tissue of the PAS group was significantly lower than that of the control group (P＜0.05). Conclusion GNA13 has the potential to become a prenatal predictive indicator for invasive PAS. The enhanced invasion and migration capacity of PAS trophoblast cells may be associated with low expression of GNA13.